P3/P3N-PIPO of PVY interacting with BI-1 inhibits the degradation of NIb by ATG6 to facilitate virus replication in N. benthamiana - Qing, Zhen; Ahmad, Shakeel; Chen, Yuemeng; Liang, Qingmin; Zhang, Lijuan; Chen, Baoshan; Wen, Ronghui (Frontiers in Plant Science, 2023)
Autophagy not only plays an antiviral role but also can be utilized by viruses to facilitate virus infection. However, the underlying mechanism of potato virus Y (PVY) infection against plant autophagy remains unclear. In this study, we investigated P3 and P3N-PIPO of PVY can interact with the Bax inhibitor 1 (BI-1) of N. benthamiana. However, BI-1 knockout mutant showed better growth and development ability. In addition, when the BI-1 gene was knocked out or knocked down in N. benthamiana, the PVY-infected mutant showed milder symptoms and lower virus accumulation. Analysis of transcriptome data showed that the deletion of NbBI-1 weakened the gene expression regulation induced by PVY infection and NbBI-1 may reduce the mRNA level of NbATG6 by regulated IRE1-dependent decay (RIDD) in PVY-infected N. benthamiana. The expression level of the ATG6 gene of PVY-infected WT was significantly down-regulated, relative to the PVY-infected mutant. Further results showed that ATG6 of N. benthamiana can degrade NIb, the RNA-dependent RNA polymerase (RdRp) of PVY. NbATG6 has a higher mRNA level in PVY-infected BI-1 knockout mutants than in PVY-infected WT. The results concluded that the interaction of P3 and/or P3N-PIPO of PVY with BI-1 decrease the expression of the ATG6 gene might be mediated by RIDD, which inhibits the degradation of viral NIb and enhances viral replication.